Reasoning Method of the Indonesian Ulama' Council And Muhammadiyah in Determining Smoking Laws - Sri Mulyani (Saniya Institute, 2024)
This paper studies the reasoning methods of the Indonesian Ulema Council (MUI) and Muhammadiyah (MTT) to explore the law of smoking thoroughly. In determining the law of smoking the fuqaha differ in opinion, this is due to differences in the istinbath methods they use to issue regulations on issues that are not found in the Qur'an and Sunnah. In finding the law of smoking the Indonesian Ulema Council and Muhammadiyah used bayani, talili, and istislahi methods. These two organizations both use dilalah'am surat al-A'raf verse 157, that cigarettes are included in the category of al-habit, namely something bad and vile, then surat al-Isra' verses 26-27, about the prohibition of wasting wealth. They also use maqasid al-shari'ah as the basis for the ban on smoking, although in this case, Muhammadiyah is clearer and more explicit, while MUI appears to quote fiqhiyah rules. Then Muhammadiyah added Surah al-Baqarah verse 195 and al-Nisa'verse 29 as well as the hadith narrated by Ahmad and Abu Daud, as one of the arguments for the prohibition of smoking. MUI did not quote the two verses and hadith as evidence for the prohibition of smoking. MUI quotes many fiqhiyah rules while Muhammadiyah does not quote them at all.